Effect of PGF 2alpha and antibiotics in ameliorating postpartum metritis in Murrah buffaloes - ABDULLAH, FAYAZ; TIWARl, R P (The Indian Journal of Animal Reproduction, 2007)
The study was conducted on 40 postpartum Murrah buffaloes suffering with metritis. Animals were divided in to four groups, each consisting of 10 animals. Buffaloes in group I were treated with oxytetracycline by intramuscular and intrauterine route for 3 days. Buffaloes in group II were treated with prostaglandin F 2a @ 25 mg intramuscular as a single dose. Buffaloes in group III were given combination of oxytetracycline as in group I and prostaglandin F pas in group II. Group IV buffaloes were kept as control. Efficacy of treatments was adjudged on the basis of clearance ofuterine discharge, uterine involution and onset of postpartum estrus. The difference for clearance of uterine discharge, uterine involution and onset of estrus was significant (P<0.05) between control and three treatment groups (I, II and III ).